STROMAL CELLS OF FAT TISSUE FOR REGENERATIVE SURGERY - V. B. Karpuk; V. A. Porhanov; M. D. Perova; I. V. Gilevich (Инновационная медицина Кубани)
Background. Generalize modern data on the current opportunities and the perspective application directions of stem/stromal cells of fat tissue in regenerative surgery.Results. Preclinical and clinical developments of cellular transplantology techniques and tissue engineering with use of the cultivated multipotent mesenchymal stromal cells of fat tissue and freshly isolated stromal vascular fraction of fat tissue in plastic surgery, maxillofacial surgery, orthopedics, neurosurgery, coloproctology, urology, thoracic surgery, cardiac surgery are presented.Conclusion. Transplantation of stromal vascular fraction of fat tissue for which releasing we do not perform cultivation of cells out of a human body is a safe and effective regenerative technology with an application potential in the wide range of surgical areas.